2010
DOI: 10.1097/gme.0b013e3181dd55b0
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sleep difficulty during the menopausal transition

Abstract: Objective To examine the relationship between menopausal transition status and self-reported sleep difficulty. Methods Using data on women participating in the Medical Research Council National Survey of Health and Development who have been followed up from birth in March 1946 (n = 962), relationships between menopausal transition status and self-reported sleep difficulty were assessed annually between ages 48 – 54. Results Menopausal transition status was related to severe self-reported sleep difficulty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 35 publications
2
68
4
1
Order By: Relevance
“…Instead, vasomotor symptoms, which increased markedly in women entering postmenopause, and depressive symptoms were the most important risk factors for impaired sleep quality. Menopausal transition has been documented as an important hallmark for increased risk for sleep disturbances [5][6][7]. Furthermore, concurrent vasomotor symptoms add to the risk [9][10][11]24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, vasomotor symptoms, which increased markedly in women entering postmenopause, and depressive symptoms were the most important risk factors for impaired sleep quality. Menopausal transition has been documented as an important hallmark for increased risk for sleep disturbances [5][6][7]. Furthermore, concurrent vasomotor symptoms add to the risk [9][10][11]24].…”
Section: Discussionmentioning
confidence: 99%
“…Around 40-60% of women report sleep impairment during menopause [4]. Although both menopausal transition [5][6][7] and aging [8] increase sleep disturbances, etiology in menopausal women is probably multifactorial. The most common menopausal complaints, nocturnal vasomotor symptoms, are associated with poor sleep [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…About 30 % of adults have one or more symptoms of insomnia, according to the American Academy of Sleep Medicine [89], and these symptoms are more prevalent in women, particularly in mid-life [90][91][92][93]. While a high prevalence of poor sleep quality in mid-life women is well-documented, several welldesigned studies concluded that influences of both age and menopausal status on poor sleep were modest [92,93].…”
Section: Depression and Poor Sleepmentioning
confidence: 99%
“…About 30 % of adults have one or more symptoms of insomnia, according to the American Academy of Sleep Medicine [89], and these symptoms are more prevalent in women, particularly in mid-life [90][91][92][93]. While a high prevalence of poor sleep quality in mid-life women is well-documented, several welldesigned studies concluded that influences of both age and menopausal status on poor sleep were modest [92,93]. In addition, while there is considerable evidence that sleep difficulties are correlated with depressive symptoms, poor sleep is a core symptom of clinical depression [94,95], which frequently makes it difficult to determine whether sleep difficulties are a component of or independent of depressed mood or clinical depression.…”
Section: Depression and Poor Sleepmentioning
confidence: 99%
“…Cutoff scores of 5 and 8 have been reported to indicate poor sleep quality; 20,21 the higher cutoff point was used in exploratory analyses because of previous studies suggesting that self-reported sleep disturbance is common among perimenopausal and postmenopausal women. [22][23][24] Eighty percent of the women in this sample had a PSQI global score of greater than 5, and 49% had scores higher than 8.…”
Section: Baseline Characteristicsmentioning
confidence: 99%